Multicultural Leadership in Islamic Boarding School Education: Strategies for Accommodating Children's Ethnic Learning Needs in - Novi Andini; Ali Pirdaus; Dian Nisa Istofa (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
This study examines the implementation of multicultural leadership in accommodating the learning needs of Suku Anak Dalam (SAD) students at Pondok Pesantren Riyadhusshalihin, Sarolangun Regency, Jambi Province. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation involving the pesantren leader, teachers, boarding administrators, and indigenous students. The findings indicate that the pesantren implemented inclusive and humanistic leadership practices by promoting equal educational access, cultural sensitivity, emotional support, and non-discriminatory learning environments. Adaptive learning strategies, including flexible instructional methods, simplified communication, continuous mentoring, and gradual social integration, enabled indigenous students to participate more effectively in educational activities while fostering their emotional adjustment. These practices also strengthened tolerance, intercultural understanding, and social inclusion within the pesantren community. This study contributes to the literature by providing empirical evidence on how multicultural leadership can support inclusive education for indigenous students within the context of Indonesian Islamic boarding schools, an area that remains underexplored. However, the findings are limited to a single-case study conducted in one pesantren and therefore cannot be generalised to all educational settings. Future research is recommended to examine multicultural leadership across different pesantren or other educational institutions using comparative or mixed-method approaches to obtain broader insights